A denúncia da voz ao ouvido: a imersão do gênero conto no romance Dom Casmurro, de Machado de Assis - Avrechack, Mariluz Marçolla Ferreira (2023)
This research aims to analyze the hybrid way in which the form of the short story emerges in conjunction with the novel Dom Casmurro (1899), by Machado de Assis (1839-1908). In addition to highlighting the melancholy voice of the narrator who complains about being listened to performative, it is based on two hypotheses. First, the story of the novel has its origins in the embryonic short story, entitled “O agregado (capítulo de um livro inédito)”, and involves a ciphered and obscure narrative that weaves two stories, one superficial which seeks to engender Capitu's adultery, and another read between the lines, which safeguards the melancholy and poetic enunciation, arising from Casmurro's voice. The second hypothesis deals with the enunciative question setting up a triad of voices that attempt to reconstitute bygone times in an enigmatic and persuasive way, which can only be captured from a performative reading that fills empty places or non-places in the novelized narrative. To answer the research problem and reach such hypotheses, the theories of Edgar Allan Poe (2009) and Ricardo Piglia (2004) about the short story are discussed. The issue of enunciation is based on the postulations of Émile Benveniste (1989) and Paul Zumthor (2007), in correlation with the ideas of Wolfgang Iser (1999) regarding the role of the reader. The axis dealing with voice and auditory activity takes up Paul Zumthor (2007) and adds Adriana Cavarero (2011) to the discussion. The investigation is based on a qualitative approach; basic in nature, exploratory, descriptive, and bibliographical. The methods used are analytical and hypotheticaldeductive. The results obtained demonstrate a silent reading that imposes degrees of performance is capable of unraveling the obscure, melancholy and triadic story manifested in Dom Casmurro. It is also understood the reader, as a filler of empty spaces in the narrative, allows the interception of visual, gestural and auditory mediations that move the plot